Digital Literacy in Elementary School: A Systematic Literature Review - Much. Fuad Saifuddin; Lovandri Dwanda Putra (Universitas Sultan Ageng Tirtayasa, 2024)
Digital literacy has become an essential competency for elementary school students in the digital era, enabling them to navigate and critically evaluate information in a safe and informed manner. This study employs a systematic literature review, guided by the PRISMA framework, to explore how digital literacy is taught in elementary schools, the learning resources and tools utilized, and the challenges and opportunities in integrating digital literacy into the curriculum. A total of 17 articles were reviewed, highlighting strategies such as interactive media, motion comics, and digital storytelling to enhance student engagement and comprehension. The findings emphasize the role of teacher preparedness, parental support, and adequate infrastructure in overcoming challenges such as limited resources and cybersecurity concerns. Opportunities for integrating digital literacy include fostering ethical awareness, promoting critical thinking, and using diverse digital tools. This research contributes valuable insights for educators and policymakers to design effective digital literacy programs tailored to the needs of young learners.